2000
DOI: 10.1046/j.1365-2796.2000.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is a strong negative prognostic factor in patients with myocardial infarction treated with thrombolytic therapy

Abstract: Abstract. Strandberg L-E, Ericsson C-G, O'Konor M-L, Bergstrand L, Lundin P, Rehnqvist N, Tornvall P (Norrta Èlje Hospital, Danderyd Hospital, the Swedish National Board of Health, Karolinska Hospital and the Karolinska Institute, Stockholm, Sweden). Diabetes mellitus is a strong negative prognostic factor in patients with myocardial infarction treated with thrombolytic therapy. J Intern Med 2000; 248: 119± 125.Objectives. To assess the long-term prognostic values of baseline demographic data, occurrence of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…All the patients were admitted to the coronary care unit at one single hospital (Danderyd Hospital). Exclusion criteria and representativeness of the patients have been reported [20]. Patients received thrombolytic treatment with either intravenous (iv) streptokinase (Streptase, Hoechst Marion Roussel, Strasbourg, France), 1.5 million U iv for 1 h, or iv front‐loaded alteplase (Actilyse, Boehringer Ingelheim, Ingelheim, Germany) given as a 10 mg bolus followed by 50 mg for 1 h and 40 mg during the subsequent 2 h. Intravenous heparin, 5000 U bolus followed by 1000 U h −1 for 24–48 h was administered after alteplase.…”
Section: Patients and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All the patients were admitted to the coronary care unit at one single hospital (Danderyd Hospital). Exclusion criteria and representativeness of the patients have been reported [20]. Patients received thrombolytic treatment with either intravenous (iv) streptokinase (Streptase, Hoechst Marion Roussel, Strasbourg, France), 1.5 million U iv for 1 h, or iv front‐loaded alteplase (Actilyse, Boehringer Ingelheim, Ingelheim, Germany) given as a 10 mg bolus followed by 50 mg for 1 h and 40 mg during the subsequent 2 h. Intravenous heparin, 5000 U bolus followed by 1000 U h −1 for 24–48 h was administered after alteplase.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…We have previously shown that age above 55 years, prevalence of diabetes mellitus and left ventricular ejection fraction (EF) below 60% are associated with a worsened prognosis in patients with myocardial infarction treated with thrombolysis [20]. In the present study, we sought to establish whether plasma concentrations of the inflammation markers CRP and fibrinogen, determined during the acute phase of myocardial infarction and 3 months after the acute event, were associated with extent of myocardial damage and long‐term prognosis amongst these patients.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were also supported in a long-term follow-up study, performed by Strandberg and associates, who showed that diabetes mellitus is a strong negative prognostic factor in patients after MI treated with thrombolytic therapy. 29 The second important finding of our study is that diabetics have worse regional left ventricular function and higher risk of left ventricular aneurysm formation compared to nondiabetics. This finding is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 60%
“…Altogether, 222 patients were included in the study between 1991 and 1995. Representativeness of the patient sample, demographic data, treatment including vectorcardiographic signs of reperfusion, left ventricular function and coronary angiographic features including TIMI flow and number of stenosed coronary arteries have been described [7]. A total of 198 (89%) of the patients underwent coronary angiography between 7 and 14 days after the acute event, of which 116 (60%) of the patients also had a planned second investigation 6 months later.…”
Section: Methodsmentioning
confidence: 99%
“…The present report is based on a study investigating coronary angiographic changes and prognosis after ST elevation myocardial infarction treated with thrombolytic therapy [7]. Our hypothesis was that the inflammatory reaction stimulated by plaque inflammation and in particular tissue injury of myocardial infarction would result in increased CAD progression in subjects with a strong inflammatory response.…”
Section: Introductionmentioning
confidence: 99%